A Few Good Reasons Why Species-Area Relationships Do Not Work for Parasites. (8th May 2014) - Strona, Giovanni; Fattorini, Simone
Abstract : Several studies failed to find strong relationships between the biological and ecological features of a host and the number of parasite species it harbours. In particular, host body size and geographical range are generally only weak predictors of parasite species richness, especially when host phylogeny and sampling effort are taken into account. These results, however, have been recently challenged by a meta-analytic study that suggested a prominent role of host body size and range extent in determining parasite species richness (species-area relationships). Here we argue that, in general, results from meta-analyses should not discourage researchers from investigating the reasons for the lack of clear patterns, thus proposing a few tentative explanations to the fact that species-area relationships are infrequent or at least difficult to be detected in most host-parasite systems. The peculiar structure of host-parasite networks, the enemy release hypothesis, the possible discrepancy between host and parasite ranges, and the evolutionary tendency of parasites towards specialization may explain why the observed patterns often do not fit those predicted by species-area relationships.